The impact of bivalent HPV vaccine on cervical intraepithelial neoplasia by deprivation in Scotland: reducing the gap. Issue 10 (29th July 2017) - Cameron, Ross L; Kavanagh, Kimberley; Cameron Watt, D; Robertson, Chris; Cuschieri, Kate; Ahmed, Syed; Pollock, Kevin G
Abstract : Background: Cervical cancer disproportionately affects women from lower socioeconomic backgrounds. A human papillomavirus (HPV) vaccination programme was introduced in Scotland in 2008 with uptake being lower and inequitable in a catch-up cohort run for the first three years of the programme compared with the routine programme. The socioeconomic differences in vaccine uptake have the potential to further increase the inequality gap in regards to cervical disease. Methods: Vaccination status was linked to demographic, cytological and colposcopic data, which are routinely collected by the Scottish HPV surveillance system. Incidence rates and relative risk of cervical intraepithelial neoplasia (CIN) 1, 2 and 3 in unvaccinated and vaccinated women were stratified by birth year and deprivation status using Poisson regression. Results: Women who received three doses of HPV vaccine have significantly decreased risk of CIN 1, 2 and 3. Vaccine effectiveness was greater in those women from the most deprived backgrounds against CIN 2 and 3 lesions. Compared with the most deprived, unvaccinated women, the relative risk of CIN 3 in fully vaccinated women in the same deprivation group was 0.29 (95% CI 0.2 to 0.43) compared with 0.62 (95% CI 0.4 to 0.97) in vaccinated women in the least-deprived group. Conclusions: The HPV vaccine is associated with significant reductions in both low-grade and high-grade CIN for all deprivation categories. However, the effect on high-grade disease was most profound in the most-deprived women. These data are welcoming and allay the concern that inequalities in cervical cancer may persist or increase following the introduction of the vaccine in Scotland.